VD_FINDINFO Jug / 2010 / 45 vom 15. Juni 2010 - VD Tribunal cantonal (2010)
LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, ÉTABLISSEMENT DE SOINS | 24 LAMal, 25 al. 2 let. a LAMal, 25 al. 2 let. b LAMal, 43 LAMal, 44 al. 1 LAMal, 50 LAMal, 89 LAMal, 29b LPFES